FISHING CAPACITY OF THE SMALL-PELAGIC FISHERY AT BANDA SEA, MOLUCCAS - Johanis Hiariey; Mulyono S Baskoro (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Excessive fishing capacity is a core issue in marine capture fisheries. In relation with the capacity issue, this study was conducted to determine annual changes of fishing capacity of the small-pelagic fishery at FMA-714 Banda Sea using time-series data of 1985 until 2006 which was analyzed using data envelopment analysis (DEA) approach. The small-pelagic fishery was found to be excess capacity in 17 out of 22 DMU. And there was indication of overcapacity in the period of 1989 until 1998. The fishery had a tendency to be not efficient with the highest score of 23.7% at DMU-1998. Consequently, alternative fishery management policies are needed to reduce fishing inputs of the fishery at the FMA-714 Banda Sea.